GOOD CORPORATE GOVERNANCE SEBAGAI PEMODERASI PENGARUH ASIMETRI INFORMASI PADA MANAJEMEN LABA - Dewi Kusuma Wardani; Wening Wahyuningtyas (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2018)
This study aims to determine the effect of information asymmetry on earnings management moderated by Good Corporate Governance (GCG). The population in this study are all property and real estate companies listed on the Indonesia Stock Exchange during the period 2012 to 2016. Samples are determined based on Purposive sampling to obtain 6 sample companies. The nature of quantitative data and data type data used is secondary data. Methods of data analysis in research used is linear regression and Moderated Regression Analysis (MRA). Test results showed that information asymmetry has a significant positive effect on earnings management with a significance level of 0.006<0.05. Good Corporate Governance (GCG) is proxied by factor score able to weaken the relationship between information asymmetry to earnings management with significance level 0,041< 0,05, so Good Corporate Governance (GCG) is quasi moderate variable.